Analisis Return on Asset (ROA) , Return on Equity (ROE) dan Corporate Social Responsibility (CSR) yang mempengaruhi Nilai Perusahaan pada Perusahaan Manufaktur - Elloni Shenurti; Desyi Erawati; Sutanti Nur Kholifah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This study aims to determine and analyze the effect of Return On Assets (ROA), Return On Equity (ROE) and Corporate Social Responsibility (CSR) on firm value. This research was conducted at manufacturing companies by taking a sample of 20 companies listed on the Indonesia Stock Exchange with the period 2013-2017. The sampling technique was carried out by using purposive sampling method. The results of this study indicate, based on the analysis found that Return On Assets and Return On Equity are not significant to company performance, but CSR has an effect on firm value.